Integrin Adhesions Suppress Syncytium Formation in the Drosophila Larval Epidermis. - Wang, Y.; Antunes, M.; Anderson, A.E.; Kadrmas, J.L.; Jacinto, A.; Galko, M.J. (Current Biology, 2015)
Integrins are critical for barrier epithelial architecture. Integrin loss in vertebrate skin leads to blistering and wound healing defects. However, how integrins and associated proteins maintain the regular morphology of epithelia is not well understood. We found that targeted knockdown of the integrin focal adhesion (FA) complex components ?-integrin, PINCH, and integrin-linked kinase (ILK) caused formation of multinucleate epidermal cells within the Drosophila larval epidermis. This phenotype was specific to the integrin FA complex and not due to secondary effects on polarity or junctional structures. The multinucleate cells resembled the syncytia caused by physical wounding. Live imaging of wound-induced syncytium formation in the pupal epidermis suggested direct membrane breakdown leading to cell-cell fusion and consequent mixing of cytoplasmic contents. Activation of Jun N-terminal kinase (JNK) signaling, which occurs upon wounding, also correlated with syncytium formation induced by PINCH knockdown. Further, ectopic JNK activation directly caused epidermal syncytium formation. No mode of syncytium formation, including that induced by wounding, genetic loss of FA proteins, or local JNK hyperactivation, involved misregulation of mitosis or apoptosis. Finally, the mechanism of epidermal syncytium formation following JNK hyperactivation and wounding appeared to be direct disassembly of FA complexes. In conclusion, the loss-of-function phenotype of integrin FA components in the larval epidermis resembles a wound. Integrin FA loss in mouse and human skin also causes a wound-like appearance. Our results reveal a novel and unexpected role for proper integrin-based adhesion in suppressing larval epidermal cell-cell fusion-a role that may be conserved in other epithelia.